Metal organic framework doped Spiro-OMeTAD with increased conductivity for improving perovskite solar cell performance. (August 2019) - Li, Mengru; Wang, Jiaqi; Jiang, Aifeng; Xia, Debin; Du, Xi; Dong, Yayu; Wang, Ping; Fan, Ruiqing; Yang, Yulin
Graphical abstract: Highlights: [In0.5 K(3-qlc)Cl1.5 (H2 O)0.5 ]2n (In10) is firstly used to oxidize Spiro-OMeTAD. The film presented improved conductivity, enhanced charge transport. The modified PSCs exhibit improved efficiency (14.1–17.0%). Abstract: In this work, a metal–organic framework, namely, [In0.5 K(3-qlc)Cl1.5 (H2 O)0.5 ]2n, (In10) is first incorporated into 2, 2′, 7, 7′-tetrakis(N, N′-di-p-methoxyphenylamine)-9, 9′-spirobifluorene (Spiro-OMeTAD). Through the simple and effective strategy, Spiro-OMeTAD oxidation is achieved and the conductivity of corresponding hole transport layer is increased, which favors the charge transport and suppresses charge recombination of perovskite solar cells (PSCs). Besides, due to the intense visible photoluminescence feature of In10, its addition can enhance the light response of perovskite solar cell. Furthermore, the modified PSCs exhibit an obviously improved device performance with short-current density (Jsc ), open circuit voltage (Voc ), and fill factor (FF) increasing from 22.7 to 24.3 mA cm −2, 0.95 to 1.0 V, and 0.65 to 0.70, respectively. As a result, the power conversion efficiency (PCE) exhibits 20% enhancement from 14.1 to 17.0%.